MANAJEMEN LABORATORIUM: MENGATASI DINAMIKA EMOSIONAL DI TEMPAT KERJA ILMIAH - Zulpadrianto, Zulpadrianto; Usdarisman, Usdarisman (UIN Imam Bonjol Padang, 2024)
Laboratories are complex environments, where social interactions and professional demands blend with performance pressures and organizational hierarchies. Behind the seemingly objective scientific activity, there are emotional dynamics that influence individual behavior, one of which is embodied shame. Based on concepts discussed by Ruebottom and Toubiana (2024), this article explores the impact of shame on laboratory management. Internalized shame can negatively impact laboratory dynamics by inhibiting collaboration, lowering emotional energy and creating a less productive work environment. Individuals who feel shame tend to shrink emotionally and physically, which inhibits their potential to innovate and collaborate effectively. To address this issue, labs must create a psychologically safe environment, where members feel supported and free from fear to conduct experiments. Inclusive leadership that supports all groups, as well as providing opportunities for reflection and personal growth, can help reduce internalized shame. With the right management strategies, laboratories can become more inclusive and supportive places, which not only improves the emotional well-being of laboratory members, but also fosters scientific innovation and better collaboration